Efficiency Comparison of Network Simulators. - Alsaleem, Maan y Anad; Yaseen, Dhafer Sabah; Aziz, Samahfakhri (International Journal of Advanced Science and Technology, 2019)
This paper presents comparative study between two network simulators (NS-3, OPNET), based on the software used and architectural simulator and Required Resources. The main focus of this paper isto compare the performance of these two simulators under similar conditions and at the same time, then measuring the (time and memory) for each simulator and recorded and analysis, to identify an optimal network simulator for the researchsociety.Keywords: Network Simulator,NS3,OPNET , NS2, Memory usage, Network size.